2020
DOI: 10.1002/anie.202012665
|View full text |Cite
|
Sign up to set email alerts
|

Strong Fermi Resonance Associated with Proton Motions Revealed by Vibrational Spectra of Asymmetric Proton‐Bound Dimers

Abstract: Infrared spectra for as eries of asymmetric protonbound dimers with protonated trimethylamine (TMA-H +)a s the proton donor were recorded and analyzed.T he frequency of the N-H + stretching mode is expected to red shift as the proton affinity of proton acceptors increases.T he observed band, however,s hows ap eculiar splitting of approximately 300 cm À1 with the intensity shifting pattern resembling at wolevel system. Theoretical investigation reveals that the observed band splitting and its extraordinarily la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…It is also gratifying to note that the quantum treatments also reproduce the ν CH region reasonably well for both TMA–H 2 O and TMA–CH 3 OH. While there is little coupling between the ν CH of TMA and H 2 O or CH 3 OH (Figure S13), there are significant couplings between CH stretches and CH 3 bends within a CH 3 group on TMA, and Fermi resonance is responsible for the extra peaks as reported recently. , …”
supporting
confidence: 65%
See 2 more Smart Citations
“…It is also gratifying to note that the quantum treatments also reproduce the ν CH region reasonably well for both TMA–H 2 O and TMA–CH 3 OH. While there is little coupling between the ν CH of TMA and H 2 O or CH 3 OH (Figure S13), there are significant couplings between CH stretches and CH 3 bends within a CH 3 group on TMA, and Fermi resonance is responsible for the extra peaks as reported recently. , …”
supporting
confidence: 65%
“…While there is little coupling between the ν CH of TMA and H 2 O or CH 3 OH (Figure S13), there are significant couplings between CH stretches and CH 3 bends within a CH 3 group on TMA, and Fermi resonance is responsible for the extra peaks as reported recently. [35][36][37]49 Note that the calculated relative intensities, especially for the ν OH related features, are less satisfactory in comparison to experiment. Whether this is due to the complexity of experiment (IR absorption combined with dissociation, saturation effects, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A general Hamiltonian has been proposed to explain intensity borrowing between a bright state (such as O–H stretching fundamental) and a set of N dark states (such as bending overtone and combination bands). For N = 2, we can recast the model Hamiltonian, in which all the coupling can be recast into H coup : Here, ε d is the averaged frequency of the two dark states, ε sd = ε s – ε d describes the resonance condition (frequency matching between stretching and centroid of dark states) and Δ = ε d – ε d 1 = ε d 2 – ε d .…”
mentioning
confidence: 99%
“…Although the frequencies of the CH stretch of 2PY are close in frequency with the hydrogen-bonded NH stretch in 2PY-(Me 2 O) and 2PY-(NH 3 ), it does not imply that CH can borrow substantial intensity from NH stretching. In a previous study on 1:1 hydrogen-bonded clusters of protonated trimethylamine (TMA) and water, methanol, and ammonia, the authors found that the strong coupling is very localized between the proton stretching fundamental and bending overtone states. Both theoretical anharmonic analysis and close comparison on the experimental spectra of TMA-H + ···H 2 O and TMA­(d 9 )-H + ···H 2 O are in favor to rule out the role of CH stretching in causing the band splitting.…”
Section: Resultsmentioning
confidence: 85%